2017
DOI: 10.2135/cropsci2016.07.0569
|View full text |Cite
|
Sign up to set email alerts
|

Maize Stalk Lodging: Morphological Determinants of Stalk Strength

Abstract: An incomplete understanding of stalk strength and stalk lodging impedes efforts to improve maize (Zea mays L.) production. To develop a more complete understanding of stalk strength, the current study examined the effect of stalk morphology on stalk bending strength. A detailed geometric analysis was conducted on five varieties of dent corn sown at five planting densities in two replicates at each of two locations near Greenville, IA, in 2013. Stalks were imaged using high‐resolution X‐ray computed tomography,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 16 publications
7
110
0
Order By: Relevance
“…A previous study from our lab describes the scanning and testing of 980 maize stalk specimens (Robertson et al , 2017). The experiments and data collected in that study were used as a starting point for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study from our lab describes the scanning and testing of 980 maize stalk specimens (Robertson et al , 2017). The experiments and data collected in that study were used as a starting point for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this study was to test the ideas put forth in our 2015 paper by using both physical and in silico experiments to more clearly determine the influence of the geometry and material properties on the structural robustness of maize stems. Another previous study from our research group identified relationships between morphological features of maize stems and their bending strength (Robertson et al , 2017). This study looks to expand on those two previous studies with more detailed specimen-specific finite element models to broaden our understanding of the effects of geometry and material properties on maize stem strength.…”
Section: Introductionmentioning
confidence: 99%
“…While this result seems counter-intuitive, there may be a simple explanation. It has been shown that stalk morphology, and in particular the section modulus, is the strongest predictor of stalk bending strength (Robertson et al, 2017), and that lignin is primarily located in the rind tissue. Section modulus is an engineering term used to describe how the mass of an object is distributed about its centroid and is used to calculate the strength and stiffness of three-dimensional structures (Robertson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that stalk morphology, and in particular the section modulus, is the strongest predictor of stalk bending strength (Robertson et al, 2017), and that lignin is primarily located in the rind tissue. Section modulus is an engineering term used to describe how the mass of an object is distributed about its centroid and is used to calculate the strength and stiffness of three-dimensional structures (Robertson et al, 2017). Since section modulus has been hypothesized to have more influence on stalk strength than tissue properties (Von Forell et al, 2015), stalks with a larger section modulus may have less need for the reinforcing role of lignin.…”
Section: Discussionmentioning
confidence: 99%
“…An incomplete understanding of stalk lodging impedes efforts to improve maize production (Robertson et al, 2017). Yield losses in maize due to stalk lodging negatively impact farmers and affect the whole society because of the instability created in the overall crop supply (Robertson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%